MAHASISWA ETNIS MINANGKABAU DALAM MENGHADAPI GEGAR BUDAYA DI BENGKULU - Dinda Ayu Ningtyas; Mukhlizar (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2024)
ABSTRACT This study aims to explain obstacles and experiences experienced by Minangkabau ethnic student who experience culture shock while studying outside their home area, aspecially in Bengkulu which has many tribes including the Rejang, Serawai, Pasemah, Lembak, and Pekal. Culture shock is a social phenomenon felt by nomads when they move and live in areas with different cultures. Culture shock occurs due to differences in perception between the original culture and the new culture. This research uses Minangkabau ethnic overseas students as the object of research, the method used is qualitative descriptive. This research explores the experiences and ways of communicating with Minangkabau ethnic students. Data was collected through in-depth interviews. The results showed several conclusions. First, Minangkabau ethnic students have obstacles in the language used, indicating that language differences are one of the main obstacles in communicating with the new environment. Second, there are differences in cultural behavior patterns between Minagkabau students and local culture. This research provides a better understanding of the barries and experiences of athnic minangkabau student who experienced culture shock. The result of this research can be the basis for developing strategies and supporting programs that facilitate the adatation and integration of overseas students in a new environment. Keywords:Minangkabau Ethnic Students, Intercultural Communication, Culture Shock